Critical race theory in the academy - Farmer, Vernon L.; Farmer, Evelyn Shepherd W.; Yancy, George; Leonardo, Zeus (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2020)
"Critical Race Theory in the Academy explores the deep implications of race and its effects on the expanse of the American social fabric and its fragile democratic process. This volume contributes to a more effective, powerful, and insightful theorization of racism across the social spectrum while furthering the movement for greater equity in higher education and beyond. The audience for this book is broad and should be of great interest and value to all Americans who fight against racism which is focused on the destruction of Black people and other people of color. Ideally, educators, scholars, and practitioners will be compelled to engage the ideas within this volume to break down the color line and challenge the problematic master narrative in education and other aspects of society. Critical Race Theory in the Academy offers current applications, debates, theories, strategies, and evolutions about critical race theory (CRT), with particular attention to CRT's intersections with the field of higher education and beyond. As a part of the CRT corpus, this volume details some of the most relevant and current topics deployed in varied disciplines of the academy, confronting the complex interplay of race, racism, education, and social justice in the twenty-first century. Specifically, the authors explore topics from health disparities, politics, religion, literature, music, social work, psychology, sports, distance learning, media bias, affirmative action, to education policies, practices and scholarship. The chapters in this volume should help navigate the tensions in the academy and beyond to work toward alleviating institutionalized racism"--